2005
DOI: 10.1007/s11103-005-8884-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Melon Alcohol Acyl-transferase Gene Family Involved in the Biosynthesis of Ester Volatiles. Identification of the Crucial Role of a Threonine Residue for Enzyme Activity*

Abstract: Volatile esters, a major class of compounds contributing to the aroma of many fruit, are synthesized by alcohol acyl-transferases (AAT). We demonstrate here that, in Charentais melon (Cucumis melo var. cantalupensis), AAT are encoded by a gene family of at least four members with amino acid identity ranging from 84% (Cm-AAT1/Cm-AAT2) and 58% (Cm-AAT1/Cm-AAT3) to only 22% (Cm-AAT1/Cm-AAT4). All encoded proteins, except Cm-AAT2, were enzymatically active upon expression in yeast and show differential substrate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
200
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(216 citation statements)
references
References 49 publications
15
200
0
1
Order By: Relevance
“…29,30) Quantitative analysis of the endogenous extracts and the headspace volatiles of different plant species indicated that only a small amount of compounds was emitted from the flower in 1 h and most of the compounds remained in the floral tissue. This observation suggests that the emission of stored volatile compounds from floral tissues may be controlled, perhaps by an excretory process regulated at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…29,30) Quantitative analysis of the endogenous extracts and the headspace volatiles of different plant species indicated that only a small amount of compounds was emitted from the flower in 1 h and most of the compounds remained in the floral tissue. This observation suggests that the emission of stored volatile compounds from floral tissues may be controlled, perhaps by an excretory process regulated at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol acyl transferases (AAT) are capable of combining various alcohols and acyl CoAs, resulting in the synthesis of a wide range of esters, thus accounting for the diversity of esters. Numerous AAT genes have been isolated and characterized in fruit and vegetables (Aharoni et al, 2000;Beekwilder et al, 2004;El-Sharkawy et al, 2005). Aliphatic esters contribute to the aroma of nearly all fruits and are emitted by vegetative tissues.…”
Section: Fatty Acid-derived and Other Lipophylic Flavor Compoundsmentioning
confidence: 99%
“…In ripe apples, alcohols constitute 6 to 16 % of the total volatiles (8), whereas esters represent, depending on the apple variety, from 80 % in Golden Delicious and Golden Reinders (14,45) to 98 % in Starking Delicious (36). Esters can have linear or branched chains, and their concentration depends on the availability of precursors (37,46,47) and on the selectivity and activity of the enzymes involved (48)(49)(50)(51). Butyl acetate, hexyl acetate, 2-methylbutyl acetate and ethyl 2-methyl--butanoate are the most important esters due to their high content and impact on apple aroma of several varieties (6,52).…”
Section: Volatile Aroma Compounds In Applementioning
confidence: 99%
“…The diversity of esters formed by AAT enzymes can be infl uenced by substrate availability, the specifi city of the enzyme, or by the variety of genes encoding ATT enzymes (49)(50)(51). Even though AAT has more affi nity for linear than for branched alcohols (17), because acetyl-CoA is the most abundant CoA in fruits, most esters are acetate esters (33,117).…”
Section: Lipoxygenase Pathwaymentioning
confidence: 99%